2009
DOI: 10.1159/000230021
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Questionnaire-Based Evaluation of the Prevalence of Urinary Incontinence in Women with Chronic Cough

Abstract: Purpose: Because chronic cough leads to repeated increases in intra-abdominal pressure, it might cause or unmask stress urinary incontinence (SUI). To test this hypothesis, we performed a cross-sectional prospective survey of women with chronic cough and female subjects without cough symptoms. Methods: A group of women with chronic cough (n = 297) presenting at a specialty asthma/allergy clinic over an 18-month period and a control group (n = 106) completed a self-administered survey that included the Urogenit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
(21 reference statements)
1
7
0
Order By: Relevance
“…A similar finding was observed in El-Hafnawy study as it was observed that patients with bronchial asthma have 9 fold rise of SUI [12]. On the other hand another prospective survey failed to show any statistically significant difference in the prevalence of UI between patients with or without chronic cough and they attributed the lack of the difference to the protective effect of urinary frequency on UI [30].…”
Section: Discussionsupporting
confidence: 83%
“…A similar finding was observed in El-Hafnawy study as it was observed that patients with bronchial asthma have 9 fold rise of SUI [12]. On the other hand another prospective survey failed to show any statistically significant difference in the prevalence of UI between patients with or without chronic cough and they attributed the lack of the difference to the protective effect of urinary frequency on UI [30].…”
Section: Discussionsupporting
confidence: 83%
“…In Canadian adults aged 30 years or older, asthma increased the risk of urinary incontinence (OR=1.35 (95% CI 1.00 to 1.95, p<0.05)) 3. However, Shariat et al ,4 reported no difference in prevalence of stress urinary incontinence in patients with chronic cough due to allergic rhinitis, sinusitis or asthma in comparison with subjects without chronic cough. In our study, the prevalence of daytime incontinence was similar in children with asthma and healthy children but prevalence of EN was higher in children with asthma younger than 6 years of age when compared with healthy controls.…”
Section: Discussionmentioning
confidence: 96%
“…2 It is known that urinary incontinence (UI) is frequently associated with cough in women, however, little information is available in the medical literature regarding the actual prevalence of this condition among women suffering chronic cough. [3][4][5] Adult women presenting to a specialty cough center (Montefiore Cough Center, Bronx, New York, USA) for evaluation of chronic cough (>8 weeks duration) comprised the study population. Stress UI was defined as the unintentional loss of urine during or immediately following an episode of coughing or other physical movement or activity.…”
Section: To the Editormentioning
confidence: 99%
“…To provide perspective, stress UI has been reported to occur in approximately 3.5% of community-dwelling women of a similar age as the subject population reported herein. 6 Previous studies investigating the prevalence of UI in women with chronic cough employed questionnaires 3,4 to obtain their data. One of those studies reported a prevalence of UI (not specifically stress UI) of 39%, 3 and another reported a prevalence of stress UI of 24% 4 .…”
Section: To the Editormentioning
confidence: 99%